2014
DOI: 10.1007/s00436-014-3975-9
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and local mucosal immune responses induced by orally delivered Bacillus subtilis spore expressing leucine aminopeptidase 2 of Clonorchis sinensis

Abstract: Human clonorchiasis caused by Clonorchis sinensis (C. sinensis) has been increasingly prevalent in recent years so that an effective measure is essential and urgent to control the infectious disease. Oral delivery of antigens from C. sinensis may be an important approach to effectively induce both systemic and local immune responses to anti-infection of the parasite. In the current study, we used Bacillus subtilis (B. subtilis) spores as a delivery vehicle to introduce leucine aminopeptidase 2 of C. sinensis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…It was suggested that ESPs are immunogenic, stimulate inflammation and promote proliferation, and suppress apoptosis [ 32 ]. Most proteins belonging to ESPs, including Cs RNASET2, Cs LAP2, and Cs NOSIP, contributed in eliciting Th2 immune response in mice [ 36 38 ]. Cytokines are important mediators in the regulation of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that ESPs are immunogenic, stimulate inflammation and promote proliferation, and suppress apoptosis [ 32 ]. Most proteins belonging to ESPs, including Cs RNASET2, Cs LAP2, and Cs NOSIP, contributed in eliciting Th2 immune response in mice [ 36 38 ]. Cytokines are important mediators in the regulation of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA sequence was inserted into the multiple clone site of the pBluescript II SK (−) plasmid [15, 27] after digestion with Sal I and Hind III. The coding sequence of Cs CP was amplified from the previously constructed pET28a (+)- Cs CP plasmid using specific primers (F: 5′-CCC AAG CTT AGC AAC ATT CCT GAA TCA G-3′, R: 5′- TAC GAG CTC TCA CAA GAT GAT CGA GGT G-3′) containing restriction sites for Hind III and Sac I (underlined).…”
Section: Methodsmentioning
confidence: 99%
“…The levels of IgG, IgG1 and IgG2a in serum were measured by an ELISA assay as described previously [15, 27]. Plates were coated with 5 μg/ml purified r Cs CP (0.05 M carbonate-bicarbonate buffer, pH 9.6) at 100 μl per well and incubated at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…As type 2 immune responses are implicated with enhancing innate and acquired immunity to helminths which mediates parasite expulsion, future work on effective anti‐helminth vaccines should focus on the induction of a robust type 2 response using suitable adjuvants and mucosal delivery strategies that present EV proteins in a manner that replicates their presentation in an infectious setting. For example, mucosal delivery strategies with orally administered nanoparticles or attenuated bacteria (or their spores) bearing surface exposed recombinant proteins derived from EVs warrants more in‐depth investigation. In the long term, package of vaccine candidates into synthetic EVs could serve as an ideal delivery system and adjuvant and would permit protection of antigens from digestive proteases in the alimentary canal while improving antigenicity by targeting specific types of antigen‐presenting cells …”
Section: Immunotherapeutic Applications and Evs As Vaccine Targetsmentioning
confidence: 99%